Internationalization strategies of emerging market multinationals in luxury fashion retailing—Case study of Shandong Ruyi Group. (26th October 2020) - Bai, Huifeng; He, Weijing; Shi, Jin; McColl, Julie; Moore, Christopher
Abstract: This article aims to examine internationalization strategies of emerging market multinationals (EMNCs) in luxury fashion retailing via their motives, direction, and entry modes. Through the case study of the Shandong Ruyi Group, data were collected using 10 in‐depth executive interviews between 2018 and 2019. The research finds that the internationalization of EMNCs in luxury fashion retailing is predominantly motivated by proactive factors, including the vision to develop to a global luxury fashion conglomerate, and the ambition to control the whole value chain from sourcing, to manufacturing and retailing. The international expansion direction in terms of production is strategic and driven by resource availability and production capability, and in terms of distribution was opportunist but is increasingly strategic. High cost entry modes are preferred, including internal organic growth, external expansion strategies such as mergers and acquisitions, and strategic alliances with a majority of equity, because of the high degree of control.